An open affective platform - Thompson, Nik; Koziniec, T.; McGill, T. (2012)
Affective computer interfaces improve human-computer interaction by enabling the communication of the user's emotional state. To this end, subtle non-verbal methods of communication provide a rich source of information which may provide valuable affective context to the human-computer interaction. Of particular note are physiological indicators of affective state, as these are objective in nature and have been demonstrated to be successful in many studies. Physiological computing may be viewed as a data acquisition and signal processing task whereby the electrical impulses or biopotentials created by the body are captured, analyzed and recorded in a suitable format for later communication. Whilst there are a number of commercially available hardware platforms to support physiological data acquisition, these all possess limitations in a few distinct areas. Not least of these is the physical form factor. For such devices to be embedded and integrated into the next generation of computer interfaces, an open physiological platform is required. This will enable future development to build upon this foundation and concentrate on novel and unique form factors and implementation environments. This paper describes the development and implementation of an open affective platform. This hardware and software solution provides the necessary functionality to measure and describe the users underlying affective state in terms of its component dimensions. This data may then be communicated to other application software, or modules within a larger affective computing application. © 2012 IEEE.